L'Architecture contemporaine en Allemagne 1970-1996 : 50 édifices. - Wang, Wilfried; Zimmermann, Gerd; de Bruyn, Gerd; Deutschen Architektur-Museum, Frankfurt (Bonn : Inter Nationes, 1997)
Aalto, Alvar ; Ando, Tadao ; Auer, Fritz ; Behnisch, Günter ; Bienefeld, Heinz ; Böhm, Gottfried ; Busse, Hans-Busso von ; van Egeraat, Erick ; Eisele, Johann ; Foster, Norman ; Fritz, Nicolas ; Gehry, Frank O. ; Gerkan, Meinhard von ; Grimshaw, Nicholas ; Gropius, Walter ; Hadid, Zaha M. ; Hertzberger, Herman ; Herzog, Thomas ; Herzog, Jacques ; Hölzinger, Johannes Peter ; Hollein, Hans ; Ito, Toyo ; Jakubeit, Barbara ; Jourdan, Jochem ; Kiessler, Uwe ; Kleihues, Josef Paul ; Kollhoff, Hans ; Timmermann, Helga ; Kulka, Peter ; Libeskind, Daniel ; Marg, Volkwin ; Meier, Richard ; Mutschler, Carlfried ; Langner, Joachim ; Peichl, Gustav ; Scharoun, Hans ; Schattner, Karljosef ; Schultes, Axel ; Seidlein, Peter C. von ; Siza, Alvaro ; Steidle, Otto ; Kiessler, Uwe ; Steidle, Otto ; Stirling, James ; Turkali, Zvonko ; Mathias-Ungers, Oswald
Frans
boek
Keywords: Duitsland